A high-strength porcelain glaze and its preparation process
By using potassium feldspar, spodumene, quartz, kaolin, etc. as the main raw materials, combined with corundum, zirconia, calcium silicate, etc. as auxiliary raw materials, and adding β-type silicon carbide whiskers and dopamine hydrochloride solutions, porcelain glaze with high strength and mechanical properties is prepared, which solves the problem of insufficient mechanical properties of the glaze of existing porcelain products and significantly improves the impact and fracture resistance of porcelain products.
Patent Information
- Application Number
- CN202411645718.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The glaze of existing porcelain products has shortcomings in terms of mechanical properties, which leads to the porcelain products being easily cracked and broken during use, affecting the quality and service life of the porcelain products.
Potassium feldspar, spodumene, quartz, and kaolin are used as main raw materials, corundum, zirconia, and calcium silicate are combined as auxiliary raw materials, and β-type silicon carbide whiskers and dopamine hydrochloride solutions are added. Through specific mixing and treatment processes, porcelain glaze with high mechanical properties is prepared.
It improves the compressive, impact and fracture resistance of porcelain products, enhances the dispersion and mechanical properties of glaze, ensures that porcelain products are not easily damaged during use, and extends the service life of porcelain products.
Smart Images

Figure BDA0005139645800000021 
Figure BDA0005139645800000051 
Figure BDA0005139645800000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porcelain product glaze preparation, and in particular, relates to a high-strength porcelain product glaze and a preparation process. Background Art
[0002] Ceramic glaze is a semi-finished product for producing porcelain. It is a very thin layer of material covering the surface of ceramics. It is formed by mixing some natural minerals and some chemical raw materials in appropriate proportions and then applying them to the surface of the ceramic body. It is then sintered at high temperature and then formed into a layer of material after a series of reactions. It has the functions of increasing the strength of porcelain products, decorating the surface of porcelain, and extending the service life. In recent years, with the rapid development of my country's porcelain industry, the output of porcelain products is currently at the forefront of the world. At the same time, various ceramic glazes are constantly emerging on the market. However, with the increase in the number of users, people's requirements for porcelain glazes and porcelain finished products are gradually increasing under the comparison of various types of porcelain products. At present, most of the existing porcelain glazes on the market meet people's demand for the appearance of porcelain finished products. Most of the porcelain finished products made of porcelain glazes have bright colors, clear patterns, exquisite and beautiful appearance, but they do not have high-strength mechanical properties, such as fracture resistance and anti-destruction performance. It is known that porcelain products with weak mechanical properties are prone to cracking, breaking or other damage during use, which leads to a decline in the quality of porcelain products and greatly affects people's use. Therefore, it is particularly necessary to provide a high-strength porcelain glaze to improve the quality of porcelain products. Summary of the invention
[0003] The purpose of the present invention is to provide a high-strength porcelain glaze and a preparation process. The present invention uses potassium feldspar, spodumene, quartz and kaolin as main raw materials, so that the glaze has a certain compressive resistance; uses corundum, zirconium oxide and calcium silicate as auxiliary raw materials, and introduces aluminum oxide components into corundum to enhance the wear resistance of the glaze; uses zirconium oxide to form a stable crystal phase in the system to prevent the lattice deformation of the glaze crystal structure; uses calcium silicate to fill the micropores and defects in the glaze to reduce the brittleness of the glaze surface; the components complement each other, and together make the porcelain products made of the glaze using the present invention have high-strength mechanical properties; in addition, the present invention selects β-SiC whiskers are used as reinforcing materials and are pretreated with dopamine hydrochloride solution, so that the prepared glaze has excellent strength and toughness. Using them in the preparation process of porcelain products can effectively improve the impact resistance and fracture resistance of porcelain products, ensuring that the porcelain products are not easily damaged in subsequent processes; and the added Tween80 and triethyl phosphate can synergistically increase the dispersibility of the prepared glaze, so that the silicon carbide whiskers are evenly dispersed and the force points are balanced, thereby consolidating the mechanical properties of the glaze and solving the problem of poor mechanical properties of porcelain products made using porcelain glazes in existing porcelain glaze preparation technologies.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A high-strength porcelain glaze, comprising the following raw materials in parts by weight:
[0006]
[0007] As a preferred embodiment of the present invention, the silicon carbide whiskers are β-type silicon carbide whiskers with an average length of 16-18 μm; and the concentration of the dopamine hydrochloride solution is 2.0 g / L.
[0008] As a preferred embodiment of the present invention, the dispersant includes at least one of Tween 80 and triethyl phosphate; preferably, the dispersant selected in the present invention is a mixture of Tween 80 and triethyl phosphate in equal parts by weight.
[0009] As a preferred solution of the present invention, the porcelain glaze further comprises deionized water.
[0010] As a preferred embodiment of the present invention, the weight of the deionized water is 1-2 times the total weight of potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide and calcium silicate.
[0011] As a preferred embodiment of the present invention, the method for preparing the porcelain glaze comprises the following steps:
[0012] S1. Evenly mix silicon carbide whiskers, anhydrous ethanol and dopamine hydrochloride solution and let it stand at a controlled temperature. After the standing, add a dispersant and ultrasonically oscillate. After the ultrasonic oscillation, stir again to obtain a mixed solution for standby use.
[0013] S2. Evenly mix potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide, calcium silicate, the blended liquid and deionized water, and perform ball milling at a controlled speed. After ball milling, the mixture is sieved, and after sieving, the mixture is stirred at a controlled speed under vacuum, and the water content is adjusted to obtain a glaze for porcelain products.
[0014] As a preferred embodiment of the present invention, the temperature of the temperature-controlled standing in step S1 is 23-25°C and the time is 22-24h; the time of the ultrasonic oscillation is 4-5min; and the time of the stirring is 0.5-1h.
[0015] As a preferred solution of the present invention, the speed of the controlled ball milling in step S2 is 500-650 r / min, and the time is 42-48 h; the screening is through a 300-500 mesh sieve.
[0016] As a preferred embodiment of the present invention, the vacuum degree of the vacuum-controlled stirring in step S2 is 0.1-0.3 MPa, the stirring speed is 100-150 r / min, and the stirring time is 0.5-1 h.
[0017] As a preferred solution of the present invention, the moisture content is adjusted to 50-60% in step S2.
[0018] Beneficial effects of the present invention:
[0019] (1) The glaze prepared by the present invention has high-strength mechanical properties. This is because the present invention uses potassium feldspar, spodumene, quartz, and kaolin as main raw materials, so that the glaze has a certain compressive resistance; uses corundum, zirconium oxide, and calcium silicate as auxiliary raw materials, and introduces alumina components with corundum to enhance the wear resistance of the glaze; zirconium oxide forms a stable crystal phase in the system to prevent the lattice deformation of the glaze crystal structure; calcium silicate fills the micropores and defects in the glaze to reduce the brittleness of the glaze surface; the components complement each other, and together make the porcelain products made of the glaze of the present invention have high-strength mechanical properties.
[0020] (2) The present invention uses β-silicon carbide whiskers as a reinforcing material and pre-treats them with a hydrochloric acid dopamine solution, so that the glaze obtained has excellent toughness. When used in the preparation process of porcelain products, it can effectively improve the impact resistance and fracture resistance of porcelain products, ensuring that the porcelain products are not easily damaged in the subsequent process. This is because β-silicon carbide whiskers have a diamond crystal structure, and there are strong covalent bonds in the molecules. They have the characteristics of high strength, high chemical stability, and high temperature resistance. Selecting them as a reinforcing material can enhance the toughness of the finished product. At the same time, adding a hydrochloric acid dopamine solution to pre-treat the β-silicon carbide whiskers forms a surface layer with strong adhesion, which strengthens the subsequent bonding strength, adhesion ability and interface compatibility between the silicon carbide whiskers and the porcelain product blank, thereby further increasing the anti-destruction ability of the final porcelain product.
[0021] (3) The present invention adds Tween80 and triethyl phosphate, which synergistically increase the dispersibility of the glaze and consolidate the mechanical properties of the glaze. This is because triethyl phosphate has a long polymer chain and can be attached to the surface of the silicon carbide whisker, playing a steric stabilizing role. At the same time, triethyl phosphate also carries a negative charge, which provides electrostatic repulsion and avoids the mutual agglomeration between the silicon carbide whiskers. On this basis, Tween80 and the silicon carbide whiskers form an adsorption layer of a certain thickness, which further prevents the silicon carbide whiskers from approaching, colliding and rubbing each other, so that they are stably dispersed, thereby increasing the dispersibility of the glaze. At the same time, because the glaze has excellent dispersibility, the silicon carbide whiskers are evenly dispersed and the force points are balanced, which further consolidates the mechanical properties of the glaze. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] A high-strength porcelain glaze, the porcelain glaze comprising the following raw materials in parts by weight:
[0025]
[0026] The silicon carbide whiskers are β-type silicon carbide whiskers with an average length of 17 μm; the concentration of the dopamine hydrochloride solution is 2.0 g / L; the dispersant is a mixture of Tween 80 and triethyl phosphate in equal parts by weight;
[0027] The porcelain glaze also includes deionized water, and the weight of the deionized water is twice the total weight of potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide and calcium silicate.
[0028] The preparation method of the porcelain glaze comprises the following steps:
[0029] S1. Mix silicon carbide whiskers, anhydrous ethanol and dopamine hydrochloride solution evenly and keep the mixture at 24°C for 22 hours. After the mixture is allowed to stand for 5 minutes, add a dispersant and ultrasonically vibrate for 0.5 hours. After the ultrasonic vibration is completed, stir the mixture for 0.5 hours to obtain a mixed solution for standby use.
[0030] S2. Evenly mix potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide, calcium silicate, the blended liquid and deionized water, and perform ball milling at a controlled speed of 500 r / min for 45 h. After ball milling, pass through a 400-mesh sieve, and after sieving, stir at a controlled speed of 100 r / min for 1 h under a vacuum of 0.3 MPa. Adjust the water content of the system to 50% to obtain a glaze for porcelain products.
[0031] Example 2
[0032] A high-strength porcelain glaze, the porcelain glaze comprising the following raw materials in parts by weight:
[0033]
[0034] The silicon carbide whiskers are β-type silicon carbide whiskers with an average length of 18 μm; the concentration of the dopamine hydrochloride solution is 2.0 g / L; the dispersant is a mixture of Tween 80 and triethyl phosphate in equal parts by weight;
[0035] The porcelain glaze also includes deionized water, and the weight of the deionized water is 1 times the total weight of potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide and calcium silicate.
[0036] The preparation method of the porcelain glaze comprises the following steps:
[0037] S1. Mix silicon carbide whiskers, anhydrous ethanol and dopamine hydrochloride solution evenly and keep the mixture at 23°C for 24 hours. After the mixture is allowed to stand for 4.5 minutes, add a dispersant and ultrasonically vibrate for 1 hour to obtain a mixed solution for later use.
[0038] S2. Evenly mix potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide, calcium silicate, the blend and deionized water, and ball-mill at a controlled speed of 650 r / min for 42 h. After ball-milling, pass through a 500-mesh sieve. After sieving, stir at a controlled speed of 150 r / min for 0.5 h under a vacuum of 0.1 MPa. Adjust the water content of the system to 60% to obtain a glaze for porcelain products.
[0039] Example 3
[0040] A high-strength porcelain glaze, the porcelain glaze comprising the following raw materials in parts by weight:
[0041]
[0042] The silicon carbide whiskers are β-type silicon carbide whiskers with an average length of 16 μm; the concentration of the dopamine hydrochloride solution is 2.0 g / L; the dispersant is a mixture of Tween 80 and triethyl phosphate in equal parts by weight;
[0043] The porcelain glaze also includes deionized water, and the weight of the deionized water is 1.5 times the total weight of potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide and calcium silicate.
[0044] The preparation method of the porcelain glaze comprises the following steps:
[0045] S1. Mix the silicon carbide whiskers, anhydrous ethanol and dopamine hydrochloride solution evenly and keep the mixture at 25°C for 23 hours. After the mixture is allowed to stand for 4 minutes, add a dispersant and ultrasonically vibrate for 4 minutes. After the ultrasonic vibration is completed, stir for 1 hour to obtain a mixed solution for standby use.
[0046] S2. Evenly mix potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide, calcium silicate, the blend and deionized water, and ball-mill at a controlled speed of 575 r / min for 48 h. After ball-milling, pass through a 300-mesh sieve. After sieving, stir at a controlled speed of 125 r / min for 1 h under a vacuum of 0.2 MPa. Adjust the water content of the system to 55% to obtain a glaze for porcelain products.
[0047] Comparative Example 1
[0048] Compared with Example 2, the difference is that in Comparative Example 1, no dopamine hydrochloride solution is added, and the other operating steps and parameters remain unchanged.
[0049] Comparative Example 2
[0050] Compared with Example 2, the difference is that the dispersant in Comparative Example 2 is Tween 80, and the other operating steps and parameters remain unchanged.
[0051] Comparative Example 3
[0052] Compared with Example 2, the difference is that the dispersant in Comparative Example 3 is triethyl phosphate, and the other operating steps and parameters remain unchanged.
[0053] Comparative Examples 4-6
[0054] Compared with Example 2, the difference is that the weight parts of corundum, zirconium oxide and calcium silicate in Comparative Examples 4-6 are as shown in Table 1, and the other operating steps and parameters remain unchanged.
[0055] Table 1
[0056] Corundum (parts by weight) Zirconium oxide (parts by weight) Calcium silicate (parts by weight) Comparative Example 4 0 6.5 6 Comparative Example 5 4.5 0 8 Comparative Example 6 4 8.5 0
[0057] Performance Testing
[0058] The ceramic bodies of the same batch and the same material were glazed with the porcelain glazes prepared in Examples 1-3 and Comparative Examples 1-6, wherein the thickness of the glaze was 3 mm; after glazing, the body was baked at 70°C for 10 hours, and then the temperature was increased to 680°C at a rate of 5°C / min, and the body was kept at this temperature for 30 minutes, and then the temperature was increased to 1100°C at a rate of 10°C / 10min, and the body was fired for 12 hours, and finally the temperature was cooled to room temperature at a rate of 5°C / 10min to obtain a porcelain product; the porcelain fragments were dried at 110°C±5°C to a constant weight, and then placed in a sealed drying oven to cool to room temperature and left for 3 hours; after 3 hours, the destructive strength and rupture modulus of the porcelain fragments were tested according to GB / T 3810.4-2006, and the results are shown in Table 2.
[0059] Table 2
[0060] Destruction strength / N Modulus of rupture / MPa Example 1 ≥1079 ≥36 Example 2 ≥1084 ≥38 Example 3 ≥1082 ≥37 Comparative Example 1 736-802 25-28 Comparative Example 2 816-890 26-29 Comparative Example 3 865-919 27-30 Comparative Example 4 921-997 28-32 Comparative Example 5 948-1018 29-34 Comparative Example 6 943-1006 29-33
[0061] It can be seen from Table 2 that the glaze prepared by the present invention has high-strength mechanical properties. In detail, it can be reflected from Comparative Examples 4-6 that the present invention uses potassium feldspar, spodumene, quartz, and kaolin as main raw materials, so that the glaze has a certain compressive resistance; uses corundum, zirconium oxide, and calcium silicate as auxiliary raw materials, and introduces alumina components with corundum to enhance the wear resistance of the glaze; zirconium oxide forms a stable crystal phase in the system to prevent the lattice deformation of the glaze crystal structure; calcium silicate is used to fill the micropores and defects in the glaze to reduce the brittleness of the glaze surface; the components complement each other, and together make the porcelain products made of the glaze using the present invention have high-strength mechanical properties.
[0062] It can be seen from Comparative Example 1 that the present invention selects β-type silicon carbide whiskers as reinforcing materials and pre-treats them with dopamine hydrochloride solution, so that the prepared glaze has excellent strength and toughness. Using it in the preparation process of porcelain products can effectively improve the impact resistance and fracture resistance of porcelain products, ensuring that the porcelain products are not easily damaged in subsequent processes.
[0063] Comparative Examples 2-3 show that the present invention adds Tween 80 and triethyl phosphate, which synergistically increase the dispersibility of the glaze and consolidate the mechanical properties of the glaze. This is because triethyl phosphate has a long polymer chain and can adhere to the surface of the silicon carbide whisker to play a steric stabilizing role. At the same time, triethyl phosphate also carries a negative charge, which provides electrostatic repulsion and avoids the mutual agglomeration of the silicon carbide whiskers. On this basis, Tween 80 and the silicon carbide whiskers form an adsorption layer of a certain thickness to further prevent the silicon carbide whiskers from approaching, colliding and rubbing each other, so that they are stably dispersed, thereby increasing the dispersibility of the glaze. At the same time, since the glaze has excellent dispersibility, the silicon carbide whiskers are evenly dispersed and the force points are balanced, which further consolidates the mechanical properties of the glaze.
[0064] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0065] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high-strength porcelain glaze, characterized in that: The porcelain glaze comprises the following raw materials in parts by weight:
2. A high-strength porcelain glaze according to claim 1, characterized in that: The average length of the silicon carbide whiskers is 16-18 μm; the concentration of the dopamine hydrochloride solution is 2.0 g / L.
3. A high-strength porcelain glaze according to claim 1, characterized in that: The dispersant includes at least one of Tween 80 and triethyl phosphate.
4. A high-strength porcelain glaze according to claim 1, characterized in that: The porcelain glaze also includes deionized water.
5. A high-strength porcelain glaze according to claim 4, characterized in that: The weight of the deionized water is 1-2 times the total weight of potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide and calcium silicate.
6. A method for preparing a high-strength porcelain glaze as claimed in any one of claims 4 to 5, characterized in that: The preparation method of the porcelain glaze comprises the following steps: S1. Evenly mix silicon carbide whiskers, anhydrous ethanol and dopamine hydrochloride solution and let it stand at a controlled temperature. After the standing, add a dispersant and ultrasonically oscillate. After the ultrasonic oscillation, stir again to obtain a mixed solution for standby use. S2. Evenly mix potassium feldspar, spodumene, quartz, kaolin, corundum, zirconium oxide, calcium silicate, the blended liquid and deionized water, and perform ball milling at a controlled speed. After ball milling, the mixture is sieved, and after sieving, the mixture is stirred at a controlled speed under vacuum, and the water content is adjusted to obtain a glaze for porcelain products.
7. The method for preparing a high-strength porcelain glaze according to claim 6, characterized in that: In step S1, the temperature of the temperature-controlled standing is 23-25°C, and the time is 22-24 hours; the time of the ultrasonic oscillation is 4-5 minutes; and the time of the stirring is 0.5-1 hour.
8. The method for preparing a high-strength porcelain glaze according to claim 6, characterized in that: In step S2, the speed of the controlled ball mill is 500-650 r / min, and the time is 42-48 h; and the screening is through a 300-500 mesh sieve.
9. The method for preparing a high-strength porcelain glaze according to claim 6, characterized in that: The vacuum degree of the vacuum-controlled stirring in step S2 is 0.1-0.3 MPa, the stirring speed is 100-150 r / min, and the stirring time is 0.5-1 h.
10. The method for preparing a high-strength porcelain glaze according to claim 6, characterized in that: The step S2 is to adjust the moisture content to 50-60%.
Citation Information
Patent Citations
High-thermal-shock-resistance ceramic vessel and preparation method thereof
CN113213887A
Porcelain with eggshell and preparation method thereof
CN115196948A